The impact of an emotion-focused training program on nursing students' emotional awareness and expression: A randomized placebo-controlled study - ŞİŞMAN, FATMA NEVİN (WILEY, 2022)
Purpose This study explores the effects of an emotion-focused training program (EFTP) and an interactive activity (placebo) on nursing students' skills in recognizing and expressing emotions. Design and Methods The research was conducted as a randomized, placebo and control group, and experimental study with repeated measurements. One hundred and twenty nursing students were randomly assigned to the groups. The EFTP was carried out for 10 sessions in the study group. Findings The emotional awareness and emotion expression scores of the students in the training group were significantly higher than those of the students in the placebo and control groups (p < 0.05). Practice Implications The EFTP can be used in the nursing undergraduate curriculum to promote emotional awareness and improve skills of emotional expression.
Keywords: emotional awareness; emotional expression; nursing students; psychodrama; SPIRITUAL INTELLIGENCE; COMMUNICATION-SKILLS; CARING BEHAVIOR; NURSES; LEVEL